Effects of acute aerobic exercise on arterial stiffness in transgender men - Yamada, Mizuki; Gam, Hyunjun; Ikegami, Nodoka; Nishikawa, Yuriko; Ishikawa, Akira; Funaki, Akiko; Matsuda, Tomoka; Kamemoto, Kayoko; Hashimoto, Yuto; Okamoto, Takanobu; Yamazaki, Hiroki; Tanaka, Hirotoshi; et al. (Frontiers in Physiology, 2023)
Testosterone replacement therapy (TRT) in transgender men (TM) results in side effects such as elevated triglycerides and increased arterial stiffness. Exercise may be useful to ameliorate such effects, but no studies have examined the effects of acute aerobic exercise in TM. This study aimed to investigate the effects of acute aerobic exercise on arterial stiffness in TM. Thirty-six participants were included, comprising 12 TM (duration of TRT: 57.4 ± 30.3 months), 12 males and 12 females. All participants performed acute aerobic exercise on a treadmill at 50% heart rate reserve for 30 minutes. Arterial stiffness as measured by brachial-ankle pulse wave velocity (baPWV) was measured before exercise (Pre), 30 minutes after exercise (Post30), and 60 minutes after exercise (Post60). Serum sex hormone levels, and serum lipid profile were determined only before exercise. Serum low-density lipoprotein cholesterol (LDL-C) levels before exercise were significantly higher in TM than in males or females (males: p<0.01; females: p<0.05). At all points, baPWV in TM was significantly higher than in females (p<0.05) and significantly lower than in males (p<0.05). However, when comparing changes in baPWV over time in each group, significant decreases in Post30 and Post60 were seen in males compared to Pre (both p<0.05), but no significant change after aerobic exercise was seen in TM or females. These results suggest that acute aerobic exercise yield different effects in TM than in males, but is unlikely to reduce arterial stiffness in TM receiving TRT.